Corporate social responsibility actions in Colombia - Lemus - Quintero, Jennifer Andrea; Carrascal - Delgado, Fabián Alfredo (Universidad Francisco de Paula Santander, 2020)
The purpose of this article is to describe the actions of Corporate Social Responsibility (CSR) that are being carried out by important companies in Colombia. The sample is represented by fifteen companies that use CSR as a business growth strategy: Grupo Bancolombia, Davivienda, Nutressa, Alpina, Postobón, Manuelita, Frisby, Grupo Orbis, Ecopetrol, Terpel, Grupo EPM, Grupo Éxito, Grupo Familia, Industrias Haceb and Amarilo. A documentary analysis was carried out on sustainability and integrated reports on sustainable management revealed by these companies during the years 2013 and 2018. The CSR actions carried out are quite similar, which is why they become a benchmark, compiled in a single document, for other companies that wish to adopt CSR as a strategic framework for their businesses.